85 TARGETING THE DYSMETABOLIC SYNDROME IN A CARDIOVASCULAR DISEASE DIABETIC COHORT WITH ROSIGLITAZONE: 1 YEAR ANALYSIS. (1st January 2005) - Aguinaldo, M.; Kronstad, D.; Cole, C.; Lyko, A.; Chao, E.; Daud, S.; Krishnamoorthy, S.; Vu, K.; Liu, W.; Magbual, R.; Petrofsky, J.; Lee, S.
Abstract : Purpose: The insulin sensitizer rosiglitazone (RSG) has been shown to improve endothelial function and reduce vascular inflammation. However, no study has prospectively looked at its overall effect on cardiovascular events. Methods: This was a non-randomized open label prospective parallel pilot study. Patients with known coronary artery disease, dysmetabolic syndrome and type 2 diabetes were recruited for the study. Patients who were medical candidates for RSG were given RSG (RSG group) in addition to routine medical care and followed in an intensive outpatient cardiovascular prevention program. If they were not medical candidates for RSG they were followed with routine medical care (control group). Results: Control group (Baseline): mean body mass index (BMI) 29.2, mean age 66, n = 18 male and 4 female, mean HgbA1c 7.47, mean low density lipoprotein level (LDL) 100. RSG Group (baseline): mean BMI 31.6, mean age 63, n = 13 male and 6 female, mean HgbA1c 7.28, mean LDL 76. After one year, the control group had a higher LDL and mean Hba1c. Control Group (1 year later): mean HgbA1c 7.63, mean LDL 96. RSG group (1 year later): mean HgbA1c 7.23, mean LDL 86. Cardiovascular events were significantly lower in the RSG group after one year: control = 9 events, RSG = 4 events, p≤.01) Mortality was significantly lower in the RSG group after one year: RSG group = no deaths, control = 7 deaths, p ≤.01). Conclusion: Lower LDL and HbA1c were seen in the RSG group. Our pilot data reveals improved cardiovascular outcomes were seen with the use of RSG. Given the small number of total cardiovascular events, short duration of this analysis and open label design, further double blind randomized placebo controlled trials with larger population over a larger period of time are warranted.